Influence of salinity on survival, growth, hemolymph osmolality, gill sodium potassium ATPase activity, and sodium potassium chloride co‐transporter expression in the redclaw crayfish Cherax quadricarinatus. Issue 2 (20th December 2020) - Rida, Reem; Zein‐Eddine, Razan; Kreydiyyeh, Sawsan; Garza de Yta, Antonio; Saoud, Imad Patrick
Abstract: The Australian redclaw crayfish Cherax quadricarinatus is a freshwater crustacean aquacultured in many countries. Redclaw crayfish are often exposed to saline waters in attempts to improve flavor, to relieve stress during transport, and to prevent or treat parasitic infestations. However, the effect of salinity on the crayfish osmoregulatory process is not well studied. In the present work, we assessed the effect of various salinities on survival, growth, and osmoregulation in redclaw crayfish. Adult crayfish were maintained at seven salinities (0, 2, 4, 6, 8, 10, and 12 ppt) for 4 weeks, and hemolymph osmolality, gill sodium potassium ATPase activity, and sodium potassium chloride cotransporter expression were assessed. In another experiment, juvenile crayfish were size sorted to similar weights and stocked at four salinities (0, 2, 4, and 6 ppt) for 8 weeks. The animals were group weighed every 2 weeks and individually weighed at the end of the eighth week. Hemolymph osmolality was constant as salinity increased from 0 to 10 ppt then a significant increase was observed at 12 ppt. Redclaw growth rate decreased with an increase in salinity from 0 to 6 ppt. Sodium potassium ATPase activity and sodium potassium chloride cotransporter expression increased with salinity increase. Although salinity might help treat ectoparasites, improve taste, and reduce transportation stress, long‐term exposure increases osmoregulatory metabolic costs and affects growth and energy consumption.